Critical Factors that Lead to Projects' Success/Failure in Global Marketplace. (2016) - Taherdoost, Hamed; Keshavarzsaleh, Abolfazl
Abstract: There is empirical evidence that project sphere has not been valued appropriately in many organizations because it seems certain that the company's projects are not unified and consequently spread across several other spheres. However, it is necessary to know how the concept of project and the project management concomitantly are made manifest in increasingly project-oriented organizations in order to achieve the organizational goals themselves. The recent study aims at a better understanding of when and why projects at a global marketplace either fail or success as well as what factors are influential. Therefore, a theoretical revision on this topic was performed. Although many studies have explored success/failure factors in projects, a few of them are comprised of the perception that to what extent project's success/failure factors are noteworthy and likewise what really are a successful project and/or a failure project. We conclude our discussion by highlighting the benefits of paying attention to success and failure factors guideline for a variety of potential practitioners in global marketplace.